2020
DOI: 10.3390/medicina56010019
|View full text |Cite
|
Sign up to set email alerts
|

Prognostication of Poor Survival After Cardiac Resynchronization Therapy

Abstract: Background and Objectives: Cardiac resynchronization therapy (CRT) is a successful treatment option for appropriately selected patients. However, one–third of recipients do not experience any positive outcome or their condition even declines. We aimed to assess preimplantation factors associated with worse survival after the CRT. Materials and Methods: This was a retrospective unicenter trial. The study cohort included 183 consecutive CRT-treated patients. Baseline demographic, clinical, electrocardiographic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Buber et al 12 found that statin use significantly reduced the risk of fatal ventricular tachycardia in patients with CRT (HR, 0.23; 95% CI, 0.13–0.40). Nevertheless, Bašinskas et al 13 reported that statin use was associated with unfavorable outcomes in patients with CRT (HR 2.98, 95% CI, 1.15–7.77). Therefore, there is no consensus in previous studies regarding the prognostic impact of statin use in cardiac patients, which may be attributed to differences in study design, race, statin type, and other confounding factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buber et al 12 found that statin use significantly reduced the risk of fatal ventricular tachycardia in patients with CRT (HR, 0.23; 95% CI, 0.13–0.40). Nevertheless, Bašinskas et al 13 reported that statin use was associated with unfavorable outcomes in patients with CRT (HR 2.98, 95% CI, 1.15–7.77). Therefore, there is no consensus in previous studies regarding the prognostic impact of statin use in cardiac patients, which may be attributed to differences in study design, race, statin type, and other confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 However, a recent study found that statin use was associated with poorer survival in patients with CRT. 13 Therefore, the evidence on the impact of statin use in CRT patients is limited and inconsistent. Of note, patients with AF may be more likely to use statins than those free of AF due to AF-related comorbidities, including coronary artery disease (CAD), stroke, and hyperlipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative incidence of clinical events was stratified by the cutoff of independent variables and compared between the two groups using a log-rank test. Univariate and multivariate Cox proportional hazard ratio regression analyses were performed to investigate the impact of ECG parameters on clinical outcomes, which were adjusted for other considerable variables, including age, male sex, ischemic etiology, left ventricular ejection fraction, the serum levels of B-type natriuretic peptide, and LBBB [ 2 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dear Editor, Basinskas and colleagues demonstrated that the ischemic etiology of heart failure was an independent predictor of mortality following cardiac resynchronization therapy [1]. Given the cost-effectiveness and urgency of heart failure, optimal patient selection for cardiac resynchronization therapy should be essential [2].…”
mentioning
confidence: 99%